Developing scientific literacy-based concept mastery instruments for high school chemistry subjects - Zulkhairi Zulkhairi; Faisal Al Banna (International Journal of Advances in Educational Research, 2024)
Research on the development of science literacy-based concept mastery instruments in eleventh-grade chemistry subjects in an even semester was conducted to (1) develop a science literacy-based concept mastery instrument, (2) determine student learning outcomes, and (3) determine teacher responses to the developed science literacy-based concept mastery instrument. The research method used is Research and Development (R&D) with a 4D development design consisting of Define, Design, Develop, and Disseminate. The research subjects consisted of four chemistry teachers: one teacher of MAN Model Banda Aceh, one teacher of MAN 2 Banda Aceh, one teacher of SMA Inshafuddin, and one teacher of SMAN 5 Banda Aceh. Limited trials on cognitive instruments developed were applied to one class XI from each school. The instruments used were interview guideline sheets, teacher needs analysis questionnaires, and multiple choice test questions based on science literacy. The results showed that the science literacy-based concept mastery instrument was declared valid and feasible to use in a limited trial with an average validation result by validators of 98.70%. The acquisition of limited trial results on students from four SMA/MAN Banda Aceh City was 84.25%, so the instrument of mastery of science literacy-based concepts developed was able to improve student learning outcomes. Teachers responded positively to the science literacy-based concept mastery instrument developed with a very good category.